Endoplasmic reticulum involvement in yeast cell death - Austriaco, Nicanor (Frontiers in Oncology, 2012)
Yeast cells undergo programmed cell death (PCD) with characteristic markers associated with apoptosis in mammalian cells including chromatin breakage, nuclear fragmentation, reactive oxygen species generation, and metacaspase activation. Though significant research has focused on mitochondrial involvement in this phenomenon, more recent work with both Saccharomyces cerevisiae and Schizosaccharomyces pombe has also implicated the endoplasmic reticulum (ER) in yeast PCD. This mini review provides an overview of ER-stress associated cell death in yeast. It begins with a description of ER structure and function in yeast before moving to a discussion of ER-stress associated cell death in both mammalian and yeast cells. Three examples of yeast cell death associated with the ER will be highlighted here including inositol starvation, lipid toxicity, and the inhibition of N-glycosylation. It closes by suggesting ways to further examine the involvement of the ER in yeast cell death.